Médicos por formação, docentes em ação : o perfil profissional e a formação do campo médico em Sergipe (1966-1973) - Silva, Patricia de Sousa Nunes (2018)
In light of the assumptions of Cultural History, this thesis aims to research the physicians who graduated in Medicine from the Faculty of Medicine of Sergipe (FMS) during the period from 1966 to 1973. More specifically, the research proposes to perform the prosopography of 24 physicians who consorted the medical profession to the teaching profession and who taught at the Federal University of Sergipe, in order to analyze the similarities and dissimilarities between the individuals and thus create the profile of the group. Therefore, we will be understanding the reason why physicians trained by FMS combine the medical profession with the teaching profession and if the specialty that each physician chose has contributed to the modernization of the medical and educational area in Sergipe. By profiling and analyzing the research subjects, who are part of the intellectuals of Sergipe, we rely on the theoretical and methodological references of the French author Jean-François Sirinelli focused on the discussions of the concepts of mediator and creator Intellectual, networks of sociability, microclimate and microcosm. In addition, it was necessary the dialogue with the reflections on memory, of Maurice Halbwachs. The sources selected were diverse, being among them: interviews, newspapers, magazines, speeches, Decrees, Minutes, Provincial Reports, photographs, messages from the President of the Province and, above all, the memoirs of the teaching physicians under analysis. This way, we hypothesize that there was a offer in the field of medical education that caused this generation of doctors to turn their eyes to the teaching profession; and that the branches of medical knowledge led them to specialize in certain areas of medicine. The fact is that, through the medical specialties, these professionals were constituting and modernizing the medical field of Sergipe through a specific technical training, substantial for the practice of local medicine. This contributed to an evolution not only from the technological point of view (diagnosis and treatment, for example), but also educational, since the doctors disseminated the knowledge acquired in the specialization courses in their classes at the Faculty of Medicine of Sergipe._________________________________________________________________________________________